PENGARUH PROFITABILITAS, STRUKTUR MODAL, LIKUIDITAS, UKURAN PERUSAHAAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2015-2019) - Amri Amrulloh; Ajeng Dwita Amalia (Universitas Budi Luhur, 2020)
This research was conducted to find out the influence between profitability, capital structure, liquidity, company size and dividend policy on firm value. This study uses banking companies as the sample, through the purposive sampling method, seven banking companies were selected as the research sample. Data analysis used multiple linear regression method with Microsoft Excel and SPSS software as auxiliary software. The results of the study say that Profitability has a positive effect on Firm Value, Capital Structure has a positive effect on Firm Value, Liquidity has no effect on Firm Value, Firm Size has no effect on Firm Value, Dividend Policy has no effect on Firm Value.